Pseudocyst of the auricle in patients with movement disorders: report of two patients with ataxia-associated auricular pseudocysts - Bryce D. Beutler; Philip R. Cohen (Mattioli1885, 2015)
Background: Pseudocyst of the auricle is a benign condition of the ear characterized by an asymptomatic, noninflammatory swelling on the lateral or anterior surface of the auricle. It typically presents as a 1 to 5 centimeter cystic lesion located within the scaphoid or triangular fossa. In most patients, the lesion develops spontaneously. However, pseudocyst of the auricle has also been associated with trauma to the ear. Purpose: We describe the clinical findings of two men who developed pseudocyst of the auricle associated with ataxia-induced trauma to their ear. We also summarize the differential diagnosis, the postulated pathogenesis, and the treatment options for this condition. Materials and methods: The features of two men with pseudocyst of the auricle are presented. Using PubMed, the following terms were searched and relevant citations assessed: ataxia, auricle, dyskinesia, ear, Friedreich's, neurological, pinna, pseudocyst, spasticity, spinocerebellar, and trauma. In addition, the literature on pseudocyst of the auricle is reviewed. Results: Pseudocyst of the auricle was observed in two men with neurological disorders: a 33-year-old Asian man with spinocerebellar ataxia and a 47-year-old Caucasian man with Friedreich's ataxia. Each patient had a history of ataxia-induced head and ear trauma. The clinical features of the lesions were sufficient to establish a diagnosis of pseudocyst of the auricle. Neither patient desired treatment. Conclusion: Pseudocyst of the auricle is a benign cystic lesion that is occasionally precipitated by trauma to the affected ear. Patients with neurological disorders, particularly those associated with ataxia and/or dyskinesias, may have an increased risk of developing the traumatic variant of the condition. Diagnosis can usually be established by clinical presentation. However, in some patients, a tissue specimen may be secured for microscopic evaluation to exclude infection or during surgical repair. Various treatment options exist for pseudocyst of the auricle, including: (1) needle aspiration-with or without subsequent injection of an irritant substance-followed by a pressure dressing and (2) surgical deroofing. Alternatively, reassurance of the benign nature of the condition and observation is a reasonable management alternative.